Application of hybrid force/position control on parallel machine for mechanical test. (February 2018) - Le Flohic, Julien; Paccot, Flavien; Bouton, Nicolas; Chanal, Hélène
Abstract: The quality of mechanical test is strongly linked to the control of boundary conditions and loaded tool path in applied forces or displacement of a tested specimen. In this article, a hybrid force/position control algorithm is adapted to parallel kinematic mechanical test machine with regards to the tested specimen behavior and realized mechanical test. This control algorithm is illustrated on a Nooru–Mohammed test performed on Gough Stewart platform and validated experimentally on a 5 bar parallel mechanism. The principle of the Nooru–Mohamed test consists in submitting a double notched concrete test part to a position slope, inducing a combination of shear and tension loading. The extra degrees of freedom of the parallel machine are used to control boundary conditions.